2014
DOI: 10.33549/physiolres.932641
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Chloride Toxicity Revisited: Effect on Certain Andrological, Endocrinological and Biochemical Parameters of Adult Male Rabbits

Abstract: The present study was devised to assess the effects of cadmium chloride (CdCl2) administration on certain andrological, endocrinological and biochemical alterations in adult male rabbits (n=24). The animals were assigned to control (n=8) and experimental (n=16) group. Experimental group was orally administered with 1.5 mg/kg body weight of CdCl2. The trials were carried out for a total of 5 weeks and blood sampling was carried out on weekly basis. A gradual decrease was noticed for body weight in the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…The present study demonstrated that four weeks of CdCl 2 exposure (5 mg/kg BW) in the absence of EBN supplement adversely affected body weight and OBWR; Cd at a lower dose has shown an adverse effect on the body weight of female rats, as demonstrated by previous studies (Nampoothiri et al, 2007;Nna et al, 2017;Samuel et al, 2011). A study conducted by Sajjad et al (2014) had found a relationship between body weight loss and concentration of Cd in hypothalamus and pituitary of Cd exposed animals. The loss in body weight due to Cd exposure may be associated with the formation of free radicals resulting in oxidative stress (Patra et al, 2011).…”
Section: Results and Discussion Body And Ovary Weightsupporting
confidence: 79%
“…The present study demonstrated that four weeks of CdCl 2 exposure (5 mg/kg BW) in the absence of EBN supplement adversely affected body weight and OBWR; Cd at a lower dose has shown an adverse effect on the body weight of female rats, as demonstrated by previous studies (Nampoothiri et al, 2007;Nna et al, 2017;Samuel et al, 2011). A study conducted by Sajjad et al (2014) had found a relationship between body weight loss and concentration of Cd in hypothalamus and pituitary of Cd exposed animals. The loss in body weight due to Cd exposure may be associated with the formation of free radicals resulting in oxidative stress (Patra et al, 2011).…”
Section: Results and Discussion Body And Ovary Weightsupporting
confidence: 79%
“…(1) it is noticed that the treatment of rats with cadmium chloride led to a significant increase (P≤ 0.05) in the level of ALT, AST and ALP compared to the control group. These results agreed with the results of Mohamed et al [20] , And Sajjad et al [21] . who found that levels of liver enzymes increased significantly in the group of animals treated with cadmium chloride due to the occurrence of hepatocyte toxicity.…”
Section: Image (6) Section Of the Rat Liver Of The Group Treated With Cadmium Chloride And Mustard Seed Extract Showing The Central Vein supporting
confidence: 93%
“…Testicular tissue is particularly susceptible to cadmium-induced damage. Cd causes degeneration of rats' epididymis, seminal vesicles and spermatozoa (Sajjad et al, 2014).…”
mentioning
confidence: 98%
“…Testicular tissue is particularly susceptible to cadmium-induced damage. Cd causes degeneration of rats' epididymis, seminal vesicles and spermatozoa (Sajjad et al, 2014).Cd, other heavy metals and oestrogenic-based compounds may explain the recent deterioration in male fertility in industrialised regions in the form of sperm count and testicular function reduction. This may involve the fact that Cd disrupts endocrine control of testicular tissue and induces oxidative damage (Siu et al, 2009).Cd exposure is linked with the generation of free radicals in acute toxicity and reactive oxygen species (ROS) in chronic toxicity.…”
mentioning
confidence: 99%